Double apple-peel intestinal atresia - Keigo Yada; Hiroki Mori; Hiroki Ishibashi (Journal of Pediatric Surgery Case Reports, 2018)
In this paper, we discuss the first case with double apple-peel atresia (IIIb + IIIb). At 31 weeks, the female neonate was given birth with body weight of 1662 g. On day 4, the open laparotomy was performed with preoperative diagnosis of intestinal atresia. At laparotomy, the proximal jejunum ended as a blind pouch about 2 cm from the ligament of Treitz. Also, There were two apple-peel shaped small intestine. The one apple-peel intestine was considered to be the middle segment, and it was anastomosed with proximal jejunum and the another apple-peel intestine. Postoperatively, the abdominal distention and the triple-bubble sign continued. As the ‘reverse’ anastomosis of the middle apple-peel segment was suspected, reoperation was performed on day 16. At laparotomy, the mesentery of middle apple-peel segment was twisted, and the ‘reverse’ anastomosis was confirmed. The re-anastomosis of the middle apple-peel segment was performed (apple-peel portion to the proximal jejunum, and the blind pouch to the another apple-peel intestine). After the reoperation, postoperative course was favorable and she was discharged home on day 51. This case suggests that apple peel intestine must locate ‘distal’ to the closed site, even in the ‘double’ apple peel atresia. Keywords: Low birth weight, Reverse anastomosis